Pengembangan APE KECEMUK (Kereta Cerdas Musik) Untuk Stimulasi Anak Berkebutuhan Khusus - Eunice Priscila Br Bangun; Artha Mahindra Diputera; Ines Manalu; Fachri Syaputra; Elsa Sofhiray Manurung; Asmarani Purba (Jurnal Usia Dini, 2025)
This study aimed to develop the Smart Music Train Educational Play Tool (KECEMUK) as a stimulation medium for children with special needs, particularly children with Attention Deficit Hyperactivity Disorder (ADHD). The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The analysis stage was conducted through observations and interviews to identify children's needs and learning conditions. The design stage produced a train-shaped educational play tool equipped with percussion musical instruments. The product was then developed and validated by media experts, material experts, and early childhood education practitioners. After revisions, the product was implemented with Group B children aged 5–6 years at Bina Ananda Mandiri Marelan Foundation. Data were collected through observations, interviews, and questionnaires and analyzed descriptively using percentage techniques. The findings revealed that KECEMUK achieved a feasibility score of 77%, categorized as very good. The use of KECEMUK increased children's interest in music learning activities, encouraged active participation, and supported the development of social and emotional skills. Therefore, KECEMUK is feasible to be used as a music-based learning medium to stimulate the development of children with special needs.